2001
DOI: 10.1086/320111
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of Spastin Gene Mutations in Hereditary Spastic Paraplegia

Abstract: Pure hereditary spastic paraplegia (SPG) type 4 is the most common form of autosomal dominant hereditary SPG, a neurodegenerative disease characterized primarily by hyperreflexia and progressive spasticity of the lower limbs. It is caused by mutations in the gene encoding spastin, a member of the AAA family of ATPases. We have screened the spastin gene for mutations in 15 families consistent with linkage to the spastin gene locus, SPG4, and have identified 11 mutations, 10 of which are novel. Five of the mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
119
2
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 15 publications
(17 reference statements)
13
119
2
2
Order By: Relevance
“…There are almost 100 SPG4 mutations described so far, including point mutations (missense, nonsense and splice site) and small insertions and deletions, with most reported families having a unique mutation Bürger et al, 2000;Hentati et al, 2000;Lindsey et al, 2000;Svenson et al, 2001;Meijer et al, 2002;Patrono et al, 2002;Morita et al, 2002;Sauter et al, 2002;Proukakis et al, 2002]. Mutations have now been reported in all SPG4 exons, except the alternatively spliced exon 4 [Svenson et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are almost 100 SPG4 mutations described so far, including point mutations (missense, nonsense and splice site) and small insertions and deletions, with most reported families having a unique mutation Bürger et al, 2000;Hentati et al, 2000;Lindsey et al, 2000;Svenson et al, 2001;Meijer et al, 2002;Patrono et al, 2002;Morita et al, 2002;Sauter et al, 2002;Proukakis et al, 2002]. Mutations have now been reported in all SPG4 exons, except the alternatively spliced exon 4 [Svenson et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations have now been reported in all SPG4 exons, except the alternatively spliced exon 4 [Svenson et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Missense, nonsense, and splice-site mutations, as well as deletions and insertions, have all been observed. Although these mutations have been found scattered along the length of SPG4, the majority of the missense mutations are localized between exons 7 and 16 (Bürger et al 2000;Fonknechten et al 2000;Hazan et al 1999;Hentati et al 2000;Lindsey et al 2000;Svenson et al 2001). This region of SPG4 has been shown to correspond to a highly conserved ATPase domain, also called the AAA cassette,…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hazen et al (1999) identified the spastin (SPG4) gene, which encodes a new member of the AAA (ATPase associated with diverse cellular activities) protein family. After this discovery, more than 70 mutations of the SPG4 gene have been reported, including missense, nonsense, and splice-site mutations, as well as insertions and deletions (Bürger et al 2000;de Bantel et al 2001;Fonknechten et al 2000;Hazan et al 1999;Hentati et al 2000;Jiggins et al 2001;Lindsey et al 2000;Namekawa et al 2001;Santorelli et al 2000;Svenson et al 2001). Here, we present a novel missense (I344K) mutation in the SPG4 gene in a large Korean family with pure AD-HSP.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation